2017
DOI: 10.1177/1548051817707517
|View full text |Cite
|
Sign up to set email alerts
|

Why and When Empowering Leadership Has Different Effects on Employee Work Performance: The Pivotal Roles of Passion for Work and Role Breadth Self-Efficacy

Abstract: With the increasing prevalence of team-based work in organizations (Kozlowski & Bell, 2013; Mathieu, Maynard, Rapp, & Gilson, 2008), managers have to delegate power to their employees and encourage them to be more autonomous, responsive, and proactive at work. As a result, empowering leadership, which is defined as "sharing power with a view toward enhancing employees' motivation and investment in their work" (Zhang & Bartol, 2010, p. 107), has received burgeoning scholarly attention in the leadership literatu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
98
2
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(122 citation statements)
references
References 79 publications
8
98
2
2
Order By: Relevance
“…Ho, Kong, Lee, Dubreuil, and Forest (2018) found that "cooperative psychological climate" assisted in the developing harmonious passion of staff with low intrinsic inclination (p. 122). Hao, He, and Long (2018) affirmed that empowered leadership was an important factor for employee work passion.…”
Section: Factors Affecting Work Passionmentioning
confidence: 99%
“…Ho, Kong, Lee, Dubreuil, and Forest (2018) found that "cooperative psychological climate" assisted in the developing harmonious passion of staff with low intrinsic inclination (p. 122). Hao, He, and Long (2018) affirmed that empowered leadership was an important factor for employee work passion.…”
Section: Factors Affecting Work Passionmentioning
confidence: 99%
“…The research of Cheong, Spain, Yammarino, and Yun (2016) also proves that the authorization of leaders objectively increases the workload of subordinates, which causes the work stress of subordinates and leads to the decline of their work performance. Hao et al (2018) also found that since empowering leaders reinforce employees' perceived leadership expectations, employees need to work hard to prove their value, which leads to controlled work emotions and further reduces employee performance.…”
Section: Introductionmentioning
confidence: 99%
“…Secondly, empowering leaders expect employees to independently assume the authority and responsibility granted by the leaders. The process of empowerment also implies the expectation of the leaders to assume the responsibility for the subordinates, and they will show confidence and expectation for the subordinates to achieve high performance (Hao et al, 2018;Zhang & Bartol, 2010). Finally, empowering leaders encourage employees to participate in the organization's decision-making and establish a flexible and democratic management style with employees.…”
Section: Introductionmentioning
confidence: 99%
“…Studies on empowering leadership and employees outcomes relationship, mainly, focus on employees' general job related outcomes like task performance, job performance and so on (Arnold et al, 2000;Ahearne et al, 2005) ignoring specific behaviors and discretionary behaviors. Moreover, researchers have reported inconsistent results in the case of leadership and employee outcomes linkage (Boles, McKee, & McMurrian, 1997;Hao, He & Long 2018;Netemeyer, Seibert, Wang & Courtright, 2011). This scientific investigation will add to literature by considering service performance behavior and OCB as employee outcomes, less focused, while investigating the relationship of leaders' empowerment behavior and employee outcomes.…”
Section: Introductionmentioning
confidence: 99%